Synthesis and evaluation of the first fluorescent antagonists of the human P2Y2 receptor based on AR-C118925 - Conroy, Sean; Kindon, Nicholas; Glenn, Jacqueline; Stoddart, Leigh A.; Lewis, Richard James; Hill, Stephen J.; Kellam, Barrie; Stocks, Michael J. (American Chemical Society, 2018)
The human P2Y2 receptor (hP2Y2R) is a G protein-coupled receptor that shows promise as a therapeutic target for many important conditions including anti-metastatic cancer therapy and more recently for the treatment of idiopathic pulmonary fibrosis. As such, there is a need for new hP2Y2R antagonists and molecular probes to study this receptor. Herein, we report the development of a new series of non-nucleotide hP2Y2R antagonists leading to the discovery of a series of fluorescent ligands containing different linkers and fluorophores based on the known, non-nucleotide hP2Y2R antagonist AR-C118925 (1). One of these conjugates 98 displayed micromolar affinity for the hP2Y2R (pKd = 6.32 ± 0.10; n=17) using a bioluminescence energy transfer (BRET) assay. Confocal microscopy with this ligand revealed displaceable membrane labeling of astrocytoma cells expressing un-tagged hP2Y2R. These properties, make 98 one of the first tools for studying hP2Y2R distribution and organization.